2018
DOI: 10.3130/aije.83.57
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Cough Droplet Deposition Using the Cough Machine

Abstract: We developed a cough machine that can generate human-like cough to evaluate the infection risk in indoor environments. The cough expired volume, propagation distance and velocity of cough, total mass of droplets and droplet size were compared with experimental results of subjects. Using the cough machine, the droplet deposition on horizontal surfaces and the position of facial mucous membranes were measured. It was shown that the number of droplet deposited on the facial mucous membranes decreased drastically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Although the particle size of the splashed droplets with our mist sprayer is unknown, 95% of the droplets deposited up to 90 cm away from the spray point. A previous study [11] showed that most droplets are deposited at a distance of 50-60 cm when using a sprayer that simulates a cough with over 90% droplet deposition at 90 cm from the spray point, similar to our mist sprayer. In this study, the portable device was placed 50 cm away from the spray point, which suggests that the droplets were suctioned by placing the portable device at the distance with the most deposition.…”
Section: Discussionsupporting
confidence: 78%
“…Although the particle size of the splashed droplets with our mist sprayer is unknown, 95% of the droplets deposited up to 90 cm away from the spray point. A previous study [11] showed that most droplets are deposited at a distance of 50-60 cm when using a sprayer that simulates a cough with over 90% droplet deposition at 90 cm from the spray point, similar to our mist sprayer. In this study, the portable device was placed 50 cm away from the spray point, which suggests that the droplets were suctioned by placing the portable device at the distance with the most deposition.…”
Section: Discussionsupporting
confidence: 78%
“…Cough was simulated using a 0.4-MPa pressure accumulation sprayer containing 10 mL of fluorescent dye 3 4 5 . An endoscopist (height 173 cm) wearing standard personal protective equipment (PPE) performed upper gastrointestinal endoscopy.…”
Section: Figmentioning
confidence: 99%
“…8 With the endoscope inserted into the mouthpiece, saliva was sprayed in the following conditions: duration, 0.2 sec; velocity, 10.7 m/sec; volume, 75.4 mL; and pressure, 0.08 MPa. 8 Three technical repeats were completed, and the diffusion of the aerosolized droplets was photographed by a camera in a darkened room with a Polarion light. Although there was significant aerosolized droplet diffusion when using the conventional mouthpiece (Fig.…”
mentioning
confidence: 99%
“…As an experimental model, simulated saliva was sprayed from the mouth of a mannequin using a cough machine. The simulated saliva was prepared by adding 76 g of glycerin to 1 L of water [ 8 ]. With the endoscope inserted into the mouthpiece, saliva was sprayed in the following conditions: duration, 0.2 sec; velocity, 10.7 m/sec; volume, 75.4 mL; and pressure, 0.08 MPa [ 8 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation